Anterior pituitary function after adrenalectomy in patients with Cushing's syndrome. Issue 813 (July 1993) - Marazuela, M.; Cuerda, C.; Lucas, T.; Vicente, A.; Blanco, C.; Estrada, J.
Abstract : We assessed anterior pituitary function in five patients with Cushing's syndrome before and after the removal of cortisol-secreting adrenal adenomas. Before surgery, all patients lacked response of growth hormone to hypoglycaemia, four had low responses of thyrotrophin to thyrotrophin releasing hormone, three had hypogonadism and two had low prolactin reserve. After successful removal of the adrenal adenoma, all patients developed postoperative hypoadrenocorticism and recovered all impaired anterior pituitary hormones within a period of 3 months. Our results point to a direct inhibiting action of glucocorticoids at the pituitary level as the explanation for the impaired anterior pituitary function. Moreover, direct gonadal suppression by glucocorticoids may be an additional mechanism of hypogonadism in some patients.